Global Research Trends on Water Contamination by Microorganisms: A Bibliometric Analysis. - Cárdenas Tirado, Zoila Isabel (2025)
Water is an essential resource for life; however, the quality of available water on the planet has been compromised due to various factors, including microbiological contamination. Objective: To analyze the global scientific production of microbiological water contamination using bibliometric methods. Method: A search for scientific articles was conducted using the advanced query function in the Web of Science™ database, specifically in its core collection, on 26 February 2025. Data from 2000 articles were analyzed using the Bibliometrix package in R (version 4.2.1) and the Biblioshiny application (version 2.0). Results: The evaluated articles were published between 1952 and 2025, with a peak in publications in 2022. The journal Water Research stood out as the most relevant, publishing 128 articles. The Egyptian Knowledge Bank was identified as the most productive institution, while China had the highest number of contributing authors. The most cited article received 475 citations. Additionally, KeyWords Plus™ highlighted the focus of the studies on ecological and biotechnological methods for contaminant removal, as well as the presence of waterborne pathogens and their inactivation methods. Conclusions: The results show a growing interest in the development of ecological and biotechnological methods for contaminant removal and pathogen inactivation in water. The integration of artificial intelligence with real-time monitoring systems emerges as a promising strategy for improving water quality management. These findings highlight the relevance of the topic for public health and health education.